Determination and Quantification of the Vinblastine Content in Purple, Red, and White Catharanthus Roseus Leaves Using RP-HPLC Method - Rohanizah Abdul Rahim; Nor Hazwani Ahmad; Khaldun Mohammad Al Azzam; Ishak Mat (Tabriz University of Medical Sciences, 2018)
Purpose: To determine and quantify vinblastine in different varieties of Catharanthus roseus using reversed-phase HPLC method. Methods: The liquid chromatographic separation was performed using a reversed phase C18, Microsorb - MV column (250 mm x 4.6 mm, 5 µm) at room temperature and eluted with a mobile phase containing methanol - phosphate buffer (5 mM, pH 6.0) - acetonitrile with different proportion gradient elution at a flow rate of 2.0 mL min-1 and detection at 254 nm. Results: The HPLC method was utilized for the quantification of vinblastine in purple, red and white varieties of Catharanthus roseus leaves. The separation was achieved in less than 8 min. The peak confirmation was done based on the retention times and UV spectra of the reference substance. The method was validated with respect to linearity, precision, recovery, limit of detection and quantification. Results showed that the purple variety gives 1.2 and 1.5 times more vinblastine concentration compared to the white and pink varieties, respectively. Conclusion: The obtained results from different varieties are thus useful for the purpose of vinblastine production from Catharanthus roseus plant.